The Role of Self-Attitude in the Personal and Professional Development of High School Students - Zh. G. Garanina; S. I. Balyaev; M. S. Ionova (Образование и наука)
Introduction. The instability of the modern world with its rapidly changing social and economic realities requires the readiness of a person for self-change. For this reason, along with vocational education, higher education has to include the programmes to form future experts’ skills of professional self-development, which success depends on many circumstances, including self-attitude.The aim of the research presented in the publication was to define the role of self-attitude in personal and professional self-development of students in the course of their professional training in higher education institution.Methodology and research methods. Empirical methods were employed in the course of the research. The complex of psycho-diagnostic techniques was used: test-questionnaire of self-attitude by V. V. Stolin and S. R. Pantileev; tests: Life-Purpose Orientations Test by D. A. Leontiev, The General Self-Efficacy Scale by M. Jerusalem, R. Schwarzer and V. Romek, Assessment of Self-Control in Communication by M. Snyder; questionnaires: Personal Orientation Inventory by E. L. Shostrom, Ability to Self-Development by V. I. Zvereva, Willingness to SelfKnowledge and Self-Development by T. A. Ratanova and N. F. Shlyahta, Determination of level of reflexivity development by A. V. Karpov, Style of Self-Regulation Behaviour of Students by V. I. Morosanova. The obtained respondents’ responses (n = 110) were processed using methods of mathematical statistics, such as correlation and cluster analysis.Results and scientific novelty. Different theoretical approaches to the problem of self-attitude highlighted in the scientific literature are considered. The affective and cognitive components of self-attitude are emphasised. Significant correlation relationships between the characteristics of self-attitude and level of motivational readiness for self-knowledge and self-development of 2nd-4th-year students-psychologists of N. P. Ogarev Mordovia State University have been revealed. It appears to be rather attributed by the fact that the attitude of students towards themselves in many respects is defined by the level of formation of their reflexive and regulatory qualities, understanding of the purpose and meaning of life, confidence in the professional success, which provide an incentive for self-change and self-improvement. The conducted cluster analysis allowed the authors to group the students around different levels of professional self-attitude and self-development (very high, high average and stagnant). The results of the research show that positive self-attitude is one of the important factors in self-development. The process of awareness of self-worth encourages the person to periodically reflect on career prospects and implementation of plans, providing the grounds for creative self-realisation.Practical significance. The results obtained can be used by teachers and psychologists of higher educational institutions to organise psycho-pedagogical support for personal and professional self-development of students.